Analytical Study of the use of ICTs by the Users of Different University Libraries in Lucknow - Nayab, Mrs. Gausia (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
However, the reality in developing nations such as Nigeria has not been encouraging, although there have improvements in recent times. From the findings of this study, it can be seen that librarians’ use of ICTs for information service delivery depends largely on their attitude to technology. Keywords: encouraging, information service, technology, developing nations